From library with love / Farahin Zaabah - Zaabah, Farahin (Faculty of Information Management, 2014)
Love can be delivered in so many ways. Some choose to show it verbally and some prefer using physical contact. Love is not only to be shown by human to another human but also to be shown by human to another living creature in this planet. Love can be delivered using many ways such as giving a helping hand to people who are in needs or better to be known as doing charity. Charity is one of the ways to show the act of giving love to the unfortunate one. It is a very noble kind of ways in showing love. This is because, love is essential to every living things in this world. Without it, people will live a sorrow, sad and depressed life. Thus, it is important to always give love to people all around us.